Echocardiographic Particle Image Velocimetry for the Evaluation of Diastolic Function in Hypertrophic Nonobstructive Cardiomyopathy. Issue 7 (20th December 2013) - Prinz, Christian; Lehmann, Roman; Brandao da Silva, Douglas; Jurczak, Barbara; Bitter, Thomas; Faber, Lothar; Horstkotte, Dieter
<x xml:space="preserve">Abstract</x> Aims To use particle image velocimetry (PIV) echocardiography for the evaluation of diastolic dysfunction (DD) in patients with hypertrophic nonobstructive cardiomyopathy (HNCM). Methods This study included 50 individuals, thereof 30 patients with DD due to HNCM and 20 healthy individuals who served as controls. HNCM patients were divided into 3 groups according to DD severity. All subjects underwent clinical assessment, exercise testing, and standard as well as PIV echocardiography. Results Energy dissipation was higher in DD patients than in the control group. The severity of flow pattern disturbance corresponded to the degree of DD. In a subgroup of 20 HNCM patients we found significant correlations between invasive measured left ventricular end‐diastolic pressure and noninvasive PIV parameters for intraventricular pressure differences and filling. Inter‐observer variability (mean difference ± 1.96 SD) for all tested PIV measurements was good. Conclusion According to DD severity, patients with HNCM have disturbed intraventricular flow and reduced intraventricular pressure differences, consistent with a reduced intraventricular suction. PIV echocardiography appears to be feasible for detailed analysis of ventricular vortex flow in DD conditions. Further research using PIV echocardiography in different cardiac pathologies seems warranted.